Kualitas Laporan Keuangan UMKM: Analisis Empiris Menggunakan Enterprise Theory Kontekstual - Purwanto, Setiyo; Retno Wuryandari, Nur Endah (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2024)
The growth of MSMEs as the foundation of the Indonesian economy requires increasing their capacity and capabilities. The aim of this research is to evaluate factors that influence the quality of financial reports. The importance of this research lies in the effort to provide knowledge that quality financial reports are very useful for measuring, analyzing and evaluating business performance whether profit or loss and as a basis for decision making. Based on bibliometric analysis, this research explores the variables of length of business, understanding of accounting, and accounting information systems on the quality of financial reports. This research uses a quantitative analysis method with a sample of 100 respondents from MSME actors around DKI Jakarta. The data was processed using the SmartPLS 3.3 statistical application program analysis. Research findings show that length of business and understanding of accounting do not guarantee that you can present quality financial reports. However, by utilizing an accounting information system, financial reports can provide accurate data information as a basis for decision making.